Farmers’ willingness to pay for stress-resilient maize hybrids in rain-fed agro-environment in Karnataka - Kulkarni, Atul Prabhakar; Kuchanur, Prakash H.; Satihal, Dayanand G.; Zaidi, Pervez H.; Rahut, Dil B. (Indian Society of Agricultural Economics, 2023)
Although maize plays a vital role in the food, fodder, and livelihood security of millions of farmers in India, it is highly vulnerable to drought and heat stress. Maize cultivation is prevalent in stress-prone agro-ecology, where the risk of losing the yield and income of smallholder farmers is high. Development and deployment of stress-resilient maize hybrids to farmers in marginal areas are crucial for coping with drought risk. The adoption of stress-resilient varieties depends on farmers' perception of the hybrid and willingness to pay (WTP) for it. In this paper, the study has estimated WTP for stress-resilient maize hybrids using primary data collected from 180 maize-growing farm households from rain-fed agro-environments in the Indian state of Karnataka. WTP was estimated using a doublebounded dichotomous choice model, and the mean WTP worked out to 312.76/kg. Farmers are WTP 37 cent premium prices to stress-resilient maize hybrid as compared to the average price paid to conventional hybrids.